Mortality at Emergency Department of BP Koirala Institute of Health Sciences: A Retrospective Review - Yadav, AK; Rai, BK; Jirel, S; Gupta, PP; Budhathoki, SS; Malla, GB (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: The emergency department (E. D.) of any hospital is an important entry point of critically ill patients. The initial management of these patients is often challenging, and for valuable lives to be saved, the infrastructure and manpower should be up-to-date.Materials and Methods: This retrospective study was carried out from previous medical record of emergency ward of B. P. Koirala Institute of Health Sciences (BPKIHS) from April 2015 to March2016. Total duration of study was one year. Data was extracted from medical records, entered in Mescal and analyzed with SPSS software.Results: The mortality rate at the BPKIHS emergency ward was 1.05%. Their ages ranged from 10-91 years with 43% of deaths among age >60 years. There was a similar proportion of death among the males and females, with almost 90% of cases in the Australian Triage Score (ATS) 1 and 2, i.e. the most severe cases. Sepsis, chronic obstructive pulmonary disease and chronic kidney disease were the common causes of death in BPKIHS emergency ward.Conclusion: Mortality was high in ATS 1 and 2, i.e. severe cases of ED. There is a need for further exploration of the cases including the morbidity profiles at BPKIHS emergency ward. More studies are needed to come to a conclusion regarding the quality of care.